PRICE BEHAVIOUR ACROSS PLACE AND TIME: A CASE OF COCOYAM WHOLESALE MARKETING IN THE SOUTHEAST, NIGERIA - Chimaobi, Chiekezie Johnson; C, Nwankwo Eucharia; Rita, Chiekezie Njideka (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
Market prices across time and region are one of the key determinants of efficient food marketing system.Against this background, the study seeks to investigate the behaviour of market price in a period and as cocoyam moves from one place to the other. Multistage, purposive and random sampling techniques were used to select 216 respondents for the study. A well structured questionnaire was used to collect primary data for six months (time series data). Data obtained was analyzed using descriptive statistics and Co-integration analysis. The study revealed that inter market and seasonal prices of cocoyam showed a highest marketing margin (7,500) in Anambra State followed by Enugu State (6,100) and least in Imo State (4300) during the peak period. During the lean period, the highest marketing margin of6,200 was recorded in Anambra State, followed by Imo State (5,150) and least (4200) in Enugu State. The Southeast recorded grand mean marketing margins of 21,499.67 and 19,667 during peak and lean respectively. The result of co-integration analysis revealed that wholesale prices of cocoyam in rural and urban markets of Anambra and Enugu State showed evidence of integration while poor price transmission was observed in the rural and urban markets of Imo State.A breakthrough in this study will gear towards improving price transmission which forms thebedrock for marketing efficiency of cocoyam in the area.